Forest Health Status in Europe - Martin Lorenz; Volker Mues (The Scientific World Journal)
Forest health status in Europe is assessed by the International Cooperative Programme on Assessment and Monitoring of Air Pollution Effects on Forests (ICP Forests). Established by the Convention on Long-Range Transboundary Air Pollution (CLRTAP) under the United Nations Economic Commission for Europe (UNECE), the ICP Forests has been monitoring forest condition in close cooperation with the European Commission (EC) for 20 years. The present paper describes the latest results of the deposition measurements on permanent monitoring plots and of the extensive defoliation sample survey. The findings reveal marked spatial patterns in bulk and throughfall depositions of nitrate (N-NO3-), ammonium (N-NH4+), and sulfate (S-SO42-), as well as an obvious decrease in bulk and throughfall deposition of sulfate. Latest analyses of defoliation data confirm previous results, indicating a high correlation with weather extremes.